2022
DOI: 10.1007/s11440-022-01544-2
|View full text |Cite
|
Sign up to set email alerts
|

Micro-feature-motivated numerical analysis of the coupled bio-chemo-hydro-mechanical behaviour in MICP

Abstract: A coupled bio-chemo-hydro-mechanical model (BCHM) is developed to investigate the permeability reduction and stiffness improvement in soil by microbially induced calcite precipitation (MICP). Specifically, in our model based on the geometric method a link between the micro- and macroscopic features is generated. This allows the model to capture the macroscopic material property changes caused by variations in the microstructure during MICP. The developed model was calibrated and validated with the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 58 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…As discussed, while some of the mentioned processes take place at different points in time (such as during operation or post-closure), others take place simultaneously or trigger each other. Biological and chemical processes also take place and could be incorporated in PDEs [54,55] but so far, they are not considered by the TH 2 M implementation or the benchmarks in this work. In order to simulate and quantify the impact of aforementioned processes on the system consisting of the repository and geosphere, they must be considered as a whole, coupled system and not separately.…”
Section: Relevant Thm-coupled Processes In Hlw Repositoriesmentioning
confidence: 99%
“…As discussed, while some of the mentioned processes take place at different points in time (such as during operation or post-closure), others take place simultaneously or trigger each other. Biological and chemical processes also take place and could be incorporated in PDEs [54,55] but so far, they are not considered by the TH 2 M implementation or the benchmarks in this work. In order to simulate and quantify the impact of aforementioned processes on the system consisting of the repository and geosphere, they must be considered as a whole, coupled system and not separately.…”
Section: Relevant Thm-coupled Processes In Hlw Repositoriesmentioning
confidence: 99%
“…where C CaCO 3 and ρ CaCO 3 [ML −3 ] present the precipitated calcite concentration at the last time interval and the bulk density of precipitated calcite, respectively. The current permeability k n [L 2 ] in pore at time intervals is given by the traditional Kozeny-Carman (KC) equation [64],…”
Section: Changes In Porosity and Permeabilitymentioning
confidence: 99%
“…Wang and Nackenhorst [161] performed numerical analyses of the coupled mechanisms in MICP for soil treatment and showed that the spatial distribution of the precipitated calcite is heavily dependent on the bacterial distribution and the relation between the reaction rate and mass transport rate. In further work, Wang and Nachenhorst [162] extended their model to include both the mechanical behaviour of the medium, including the increase in stiffness with MICP, and micro-structural effects on the reaction kinetics. The comparison of simulations with experimental data showed that the coupled bio-chemo-hydro-mechanical model gave a reasonable prediction of the test results.…”
Section: Models At the Macroscalementioning
confidence: 99%